Climate effects on size‐at‐age and growth rate of Chinook Salmon (Oncorhynchus tshawytscha) in the Fraser River, Canada. (1st July 2020) - Xu, Yi; Scott Decker, A.; Parken, Charles K.; Ritchie, Lynda M.; Patterson, David A.; Fu, Caihong
Abstract: Decline in size‐at‐age of Chinook Salmon ( Oncorhynchus tshawytscha ) has been observed for many populations across the entire Northeast Pacific Ocean, and identifying external drivers of this decline is important for sustainable management of these ecologically, economically, and culturally valuable resources. We assessed size‐at‐age of 96, 939 Chinook Salmon sampled in the Fraser River watershed (Canada) from 1969 to 2017. A broad decline in size‐at‐age was confirmed across all population aggregates of Fraser River Chinook Salmon, in particular since year 2000. By developing a novel probability‐based approach to calculate age‐ and year‐specific growth rates for Fraser River Chinook Salmon and relating growth rates to environmental conditions in specific years through a machine learning method (boosted regression trees), we were able to disentangle multi‐year effects on size‐at‐age and thus identify environmental factors that were most related to the observed size‐at‐age of Chinook Salmon. Among 10 selected environmental variables, ocean salinity at Entrance Island in spring, the Aleutian Low Pressure Index and the North Pacific Current Bifurcation Index were consistently identified as important contributors for four of the seven age and population aggregate combinations. These top environmental contributors could be incorporated into future stock assessment and forecast models to improve Chinook Salmon fisheries management under climate change.